In vitro and In silico Antibacterial Potency of Eucalyptus Leaf Oil from Hybrid Clones of E. grandis with E. urophylla and E. pellita - Prayogo, Yanico Hadi; Anggini, Awanda Wira; Carolina, Anne; Togu Manurung, Elisa Ganda; Sari, Rita Kartika; Purwoko, Agus; Pasaribu, Gunawan (Applied Science and Engineering Progress, 2025)
Hybridization can introduce beneficial traits from different species, such as increased disease resistance, yield, or stress tolerance. This study aimed to describe the effect of hybridization on the essential oil yield, phytochemical components, in vitro and in silico antibacterial activity of essential oil extracted from Eucalyptus leaves from various clones against 4 different types of bacteria. The E. grandis-E. pellita clones were characterized by higher abundances of α-pinene and α-terpineol. Meanwhile, the E. grandis-E. urophylla clones were characterized by higher abundances of γ-terpinene, phellandrene, terpinen-4-ol, and caryophyllene. Clone from E. grandis-E. pellita showed the highest antibacterial against Klebsiella pneumoniae, Bacillus subtilis, and Salmonella typhi. Meanwhile, clones from E. grandis-E. urophylla showed the highest antibacterial against Staphylococcus aureus. The in silico analysis predicted two compounds, namely spathulenone and α-terpineol as the most potent bioactive compounds against four different antibacterial protein targets. This finding demonstrates the potential of Eucalyptus leaf essential oil as an antibiotic against both Gram-positive and Gram-negative bacteria, and it is expected that in the future, its activity can be enhanced by focusing on increasing the content of active compounds predicted from the in silico analysis.